A prospective cross-sectional study on parent - Female adolescent communication towards sexual and reproductive health issues in south west ethiopia: Parent perspective - Ayanos Taye; Diriba Wakjira; Gemechu Terefe; Enatfenta Sewmehone (Elsevier, 2023)
Background: Even though female adolescents can get information regarding sexual and reproductive issues from different sources, parents are the preferred source of information for most adolescents. Objective: The study was aimed at assessing the parent-female adolescent communication regarding sexual and reproductive health issues in southwest Ethiopia. Method and materials: Community-based retrospective cross-sectional study design was employed among 388 parents of a female adolescent from May 5 to 26, 2021. The data were entered into Epi data version 4.2 and analyzed by the Statistical software package for social science version 23. Bivariable and multivariable logistic regressions were done to identify factors associated with poor parent-female adolescent communication regarding sexual and reproductive health issues. Results: According to this study, 223 (61.9%) parents had poor communication on sexual and reproductive health with their female adolescents. Having no communication difficulties regarding sexual and reproductive health issues[AOR = 0.287;95 %CI:0.167-0.494], poor knowledge of SRH issues[AOR = 2.082;95 %CI:1.222-3.547], in favorable attitude towards parents- female adolescent sexual and reproductive health communication[AOR = 1.847;95 %CI:1.065-3.204], parents didn't have previous experience of sexual and reproductive health problem[AOR = 3.062;95 %CI:1.779-5.204], parents-whose female adolescent not asked about SRH issues[AOR = 0.434.;95 %CI:0.265-0.743] were the identified statically associated factors with poor parent-female adolescent communication regarding sexual and reproductive health issues. Conclusions: Despite the fact that poor parent-female adolescent communication has many impacts on sexual and reproductive health issues in female adolescents this study showed the status of poor parents-female adolescent communication regarding sexual and reproductive health issues was high. The knowledge, attitude, and communication challenges of parents regarding sexual and reproductive health concerns were found to be the identified factors associated with poor parents-female adolescent sexual and reproductive health communication practices. Thus, creating a positive atmosphere, and effective communication between parents and adolescents through empowering both parents and adolescents can improve the overall sexual and reproductive health issues of the adolescent.